Biochemical Profile and Antibacterial Examination of Freshwater Crab Scylla Serrata (FORSKAL, 1775) - Beslin, Leena Grace; G, Geni (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Natural products from the aquatic organisms provide unlimited opportunities for the production of new drugs. To verify this fact in the present study ‘the biochemical profile and antimicrobial activity of different samples of the estuarine crab, Sylla serrata’ was investigated. Biochemical study of the body parts of the crab gains substantial attention for their specificity in connection to the food values of the crab and for the evaluation of their physiological needs at different periods of life. The total protein was estimated by Lowry's method and the amount of protein was highest in the soft muscle sample (20.27mg/ml). The total sugar was estimated by the Phenol-Sulphuric acid method and it was highest in the leg sample (209.8mg/ml). The lipids of the samples were estimated by Folchs method. Lipid was highest in the shell sample (28.35mg/ml). Thin Layer chromatography was done for characterization of protein. Antibiotics are used against bacterial infections. The natural products gained importance to screen antibiotics. For this reason the antibacterial activity of the samples were tested against grampositive and gramnegative pathogenic bacterial strains. The bacterial strains like Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Enterobacter aerogenes were used as the test strains. In the present study, the ethanol extract of crab sample I showed maximum zone of inhibition (13 mm) in P. aeruginosa. The sample I showed moderate zone of inhibition (11 mm) in K.pneumoniae. The sample II showed the minimum zone of inhibition (7 mm) in P. aeruginosa. It indicated that the shell of crabs would be a good source of antimicrobial agents and would replace the existing inadequate and cost effective antibiotics. The microbial associates of crustaceans have proven to be a rich source of bioactivity with antimicrobial and cytotoxic effects. So the organism used in the present study will be the promising source to the biotechnological and pharmaceutical applications.